2012
DOI: 10.1016/j.ygcen.2012.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Rapid stress-induced inhibition of plasma testosterone in free-ranging male rufous-winged sparrows, Peucaea carpalis: Characterization, time course, and recovery

Abstract: Article (refereed) -postprintDeviche, Pierre; Gao, Sisi; Davies, Scott; Sharp, Peter J.; Dawson, Alistair. 2012Rapid stress-induced inhibition of plasma testosterone in free-ranging male rufouswinged sparrows, Peucaea carpalis: characterization, time course, and recovery. Endocrinology, 177 (1). 1-8. 10.1016/j.ygcen.2012.02.022 Contact CEH NORA team at noraceh@ceh.ac.uk General and ComparativeThe NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 67 publications
(85 reference statements)
5
47
1
Order By: Relevance
“…All birds were caught and observed between 0600 and 1600. A previous study on free-ranging breeding males of a conspecific species, the Rufous-winged Sparrow, Peucaea carpalis, found that plasma T does not change consistently during the course of the day (Deviche et al, 2012).…”
Section: Animalsmentioning
confidence: 88%
See 2 more Smart Citations
“…All birds were caught and observed between 0600 and 1600. A previous study on free-ranging breeding males of a conspecific species, the Rufous-winged Sparrow, Peucaea carpalis, found that plasma T does not change consistently during the course of the day (Deviche et al, 2012).…”
Section: Animalsmentioning
confidence: 88%
“…Mounting evidence indicates that plasma androgens can also rapidly and facultatively decrease, e.g., in response to acute stress (Deviche et al, 2010(Deviche et al, , 2012Lynn et al, 2010;Moore et al, 2002;Wingfield et al, 1982) .…”
Section: Juncos Junco Hyemalis Have Similar Plasma T Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was experimentally demonstrated by Veiga (1992) who suggested that the female-female aggression could be related to the avoidance of nest parasitism, or expelling a potential female in order to maintain its monogamous status. In addition, the fact that all birds were maintained in a barn for one week could have resulted in some variations of TS levels due to stress (Deviche et al, 2012). AN levels were low in both males and females (male mean = 0.092 ng/ml, female mean = 0.088 ng/ml) compared to levels reported in Japanese quail (male mean = 1.9 ng/ml, female mean = 2.4 ng/ml) (Ramenofsky, 1984), but did not differ substantially from AN levels reported for prelaying female blue-throats (Luscinia svecica), (Pärn et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, house sparrows implanted with testosterone and held in short days showed no suppression of cell-mediated immune activity, indicating that testosterone is not obligatorily immunosuppressive year-round in this species . Furthermore, studies in a diversity of vertebrate species have shown that stressors typically suppress testosterone levels (T), sometimes quite rapidly (Greenberg and Wingfield, 1987;Deviche et al, 2010, Deviche et al, 2012Deviche et al, 2014). Reduction on T levels has been reported after induced acute stress in reptiles (reviewed in Tokarz and Summers, 2011), and after a restraint challenge and toe-clipping in toads (Narayan et al, 2011b;Narayan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%